New Firms Evolving in the Knowledge Economy; problems and solutions around turning points - Erik Stam; Elizabeth Garnsey (Max Planck Institute for Research into Economic Systems, 2005)
This paper explores and explains the emergence and growth of new firms in the knowledge economy. The resource-based view, capabilities approach, and evolutionary economics are used as a foundation for a developmental approach. The development of the firm is conceptualized in terms of processes that include opportunity recognition, resource mobilization, resource generation and resource accumulation, which lead to the development of competences and capital in a base made up of productive, commercial and financial resources. Problems originating within or outside the firm may deplete the productive, commercial and asset base, leading to turning points in the life course of these firms. These have negative consequences when problems are not solved, but positive consequences when they lead to new solutions and the development of new competence. The empirical study shows that even in an elite sample of young fast-growing firms, most firms face turning points in their life course, and thus do not grow in a continuous way. The study shows that quantitative growth indicators do not always reveal growth problems that have been faced by new firms. Some problems do not negatively affect the employment growth of the firm, and other problems are solved before growth stagnates. The qualitative analysis shows that young firms are almost always in disequilibrium: there is almost never a perfect match between the constituents of their resource base, between input resources and requirements for expansion. This explains why continuous growth is so unlikely. Although every firm seems to grow in a unique manner, there is evidence for the presence of a limited set of necessary mechanisms for the growth of (new) firms, which work out in particular ways given the specific context and history of these firms.
Keywords: D21; M13; L23; D92; M21; 330; New firms; firm growth; theory of the firm; resource based view; firm life course; organizational crises; knowledge economy; Unternehmensgründung; Lebenszyklus; Unternehmenswachstum; Informationsgesellschaft